Internet connectivity disruption in Bosnia and Herzegovina (Bosnia and Herzegovina) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Bosnia and Herzegovina. Data sourced from IODA.
Network Disruption Incident ID: BA-2026-0053. Severity: critical. Confidence: 67%